Paradox and legitimacy in construction: how CSR reports restrict CSR practice. Issue 2 (8th April 2019) - Watts, Greg; Fernie, Scott; Dainty, Andy
Abstract : Purpose: Corporate social responsibility (CSR) is a prominent topic of debate, and yet remains subject to multiple interpretations. Despite this ambiguity, organisations need to communicate their CSR activity effectively in order to meet varied stakeholder demands, increase financial performance and in order to achieve legitimacy in the eyes of clients and various stakeholders. The purpose of this paper is to explore how CSR is communicated, and the impact such communication methods have on CSR practice. More specifically, it examines the disconnect between the rhetoric espoused in CSR reports and the actualities of the ways in which CSR is practiced. Design/methodology/approach: A qualitative content analysis of 100 CSR reports published by nine construction contractors informed the design of qualitative interviews. In total, 17 interviews were then conducted with contractors and public body clients. Findings: Strategic ambiguity explains how contractors circumvent the problem of attending to conflicting stakeholder CSR needs. However, this results in a paradox where CSR is simultaneously sustained as a corporate metric and driver, whilst being simultaneously undermined in being seen as a rhetorical device. By examining this phenomenon through the lens of legitimacy, the study reveals how both the paradox and subsequent actions of clients that this provokes, act to restrict the development of CSR practice. Originality/value: This is the first study to use the lens of legitimacy theory to analyse the relationship between CSR reporting and CSR practice in the construction industry. In revealing the CSR paradox and its ramifications the research provides a novel explanation of the lack of common understandings and manifestations of CSR within the construction sector.